miR-22 Suppresses Tumor Invasion and Metastasis in Colorectal Cancer by Targeting NLRP3 - Cong J; Gong J; Yang C; Xia Z; Zhang H (Cancer Management and Research, 2020)
Jinchun Cong,1,* Jian Gong,2,* Chuanjia Yang,3 Zhixiu Xia,1 Hong Zhang1 1Department of Colorectal Tumor Surgery, Shengjing Hospital of China Medical University, Shenyang 110004, People’s Republic of China; 2Department of Clinical Pharmacy, Shenyang Pharmaceutical University, Shenyang 110016, People’s Republic of China; 3Department of General Surgery, Shengjing Hospital of China Medical University, Shenyang 110016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Zhang Email zhanghong7919@outlook.comPurpose: This study aimed to investigate the effects of microRNA (miR)-22 on biological behaviors of colon cancer cells and to explore the relationship between miR-22 and NLRP3.Materials and Methods: First, human colon cancer HCT116 cells were transfected with a miR-22 mimic, miR-22 inhibitor, control mimic, and control inhibitor, respectively. CCK8, colony formation, and transwell assays were performed to observe cell proliferation, migration, and invasion. Western blotting was used to analyze the expression of recombinant NLRP3 (NLR family, pyrin domain-containing protein 3) and epithelial–mesenchymal transformation (EMT)-related proteins. The target relationship between miR-22 and NLRP3 was verified by double luciferase report. Second, an NLRP3 inhibitor and NLRP3 mimic were transfected into HCT116 cells, and the biological behaviors and EMT-related proteins were again observed. Finally, a nude mouse xenograft model was constructed to verify the above results.Results: In vitro, compared with the control group, administration of the miR-22 mimic significantly decreased proliferation, migration, and invasion of HCT116 cells, whereas the miR-22 inhibitor markedly increased their proliferation and invasion (p< 0.05). Levels of NLRP3, interleukin-1β (IL-1β), matrix metalloproteinase-9 (MMP-9), MMP-2, N-cadherin, and vimentin were significantly reduced after miR-22 mimic transfection (p< 0.05). Furthermore, silencing of NLRP3, a downstream gene of miR-22 in HCT116 cells, suppressed proliferation, migration, and invasion of HCT116 cells. However, overexpression of NLRP3 weakened the effects of the miR-22 mimic. In vivo, overexpression of miR-22 slowed the growth rate of tumors and reduced Ki-67 expression in tumor tissues compared with the model group (p< 0.05). In tumor tissues, overexpression of miR-22 also decreased expression of NLRP3, IL-1β, MMP-9, MMP-2, N-cadherin, and vimentin compared with the model group (p< 0.05). Overexpression of NLRP3 weakened the role of miR-22 overexpression in vivo.Conclusion: miR-22 suppresses cell proliferation, migration, and invasion in colorectal cancer by targeting NLRP3.Keywords: miR-22, NLRP3, colorectal cancer, epithelial–mesenchymal transformation, invasion